2009
DOI: 10.1016/j.rmed.2008.11.017
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of integrated use of disease-management interventions in asthma and COPD

Abstract: In spite of the heterogeneity of disease management studies in asthma and COPD care, this review showed promising improvements in quality of life and reductions in hospitalisations, especially for triple intervention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 76 publications
(100 reference statements)
8
105
0
5
Order By: Relevance
“…Our results support trends found in previous investigations 10,20 and highlight an overall improvement in the quality of care for asthma patients. Therefore, we conclude that since the implementation of the DMP for asthma in Bavaria in 2006, adherence to guidelines, symptom frequency, and pharmacotherapy have improved.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results support trends found in previous investigations 10,20 and highlight an overall improvement in the quality of care for asthma patients. Therefore, we conclude that since the implementation of the DMP for asthma in Bavaria in 2006, adherence to guidelines, symptom frequency, and pharmacotherapy have improved.…”
Section: Discussionsupporting
confidence: 91%
“…Gibson et al 10 have shown that self-management education for patients with asthma reduces hospitalization, emergency room visits, unscheduled visits to the general practitioner, disability, and nocturnal asthma, while improving the overall quality of life. Additionally, a meta-analysis by Lemmens et al 20 found evidence that multiple interventions led to a significant reduction in hospitalization, in comparison with routine care. The reduction in hospitalization may in turn save costs.…”
Section: Disease Management Programs For Patients With Asthma In Germanymentioning
confidence: 99%
“…A meta-analysis by Lemmens et al 37 found evidence that multiple interventions led to a significant reduction in hospitalization in comparison with routine care. A reduction in hospitalization may in turn save costs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews in patients with COPD have studied self-management education (11,12), integrated care (13)(14)(15), shared management between specialists and primary care physicians (16), and home care (17) in patients with stable COPD, or hospital at home for acutely ill patients with COPD exacerbations (18) or other conditions (19). Previous reviews on care transitions from hospital to home have focused on other patient populations (ie, not patients with COPD exacerbations) (20)(21)(22).…”
mentioning
confidence: 99%